2007
DOI: 10.1111/j.1346-8138.2007.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with cyclosporin administration for persistent benign migratory glossitis

Abstract: We herein describe a 54 year-old female patient with a 5-year history of persistent and painful benign migratory glossitis (BMG), which was remarkably improved by systemic administration of cyclosporin. She had noted some white patches leaving smooth denuded red areas with whitish elevated borders on the dorsum of her tongue, and finally felt strong pain. The lesion was refractory to the previous treatment with topical corticosteroid treatment for the last 2 years. Because clinicopathological findings were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 9 publications
0
39
1
5
Order By: Relevance
“…predominance of CD4-positive cells in the macrophage and T-cell infiltrate) [28]. Moreover, the resolution of both BMG and cutaneous lesions with antipsoriatic agents appears to suggest a common etiology [29]. Despite these observations, recognition of geographic tongue as a true oral expression of psoriasis has been questioned, particularly when the existence of geographic tongue predates cutaneous psoriasis by many years.…”
Section: Perioral and Oral Manifestations Of Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…predominance of CD4-positive cells in the macrophage and T-cell infiltrate) [28]. Moreover, the resolution of both BMG and cutaneous lesions with antipsoriatic agents appears to suggest a common etiology [29]. Despite these observations, recognition of geographic tongue as a true oral expression of psoriasis has been questioned, particularly when the existence of geographic tongue predates cutaneous psoriasis by many years.…”
Section: Perioral and Oral Manifestations Of Psoriasismentioning
confidence: 99%
“…Resolution of BMG and psoriatic lesions confined to the lip vermilion with topical application of 0.1% tacrolimus ointment has also been documented [22,36]. Abe et al [29] reported a therapeutic response to the administration of a systemic cyclosporine microemulsion preconcentrate of 3 mg/kg/day for the management of severely symptomatic, refractory BMG in a 54-year-old woman [37]. …”
Section: Treatmentmentioning
confidence: 99%
“…Les autres traitements utilisés et proposés dans la littéra-ture dans l'indication des langues géographiques algiques sont les corticoïdes locaux [9,1], les rétinoïdes locaux [10,1], les rétinoïdes par voie orale [11,1] et la ciclosporine per os [12,1]. Ces deux derniers traitements, bien qu'efficaces, sont disproportionnés en raison des effets indésirables potentiels.…”
Section: Discussionunclassified
“…Use of diphenhydramine, lidocaine rinse and sodium bicarbonate rinse has shown successful results in symptomatic cases of mild intensity. [16] If significant pain persists then use of topical and systemic antihistamines [17], Vitamin A acid therapy and systemic acitretin [17] systemic cyclosporine [18], topical corticosteroids [19], topical tacrolimus ointment [20] has been reported in the literature. In the present case medical intervention was planned as the tongue was symptomatic and use of 0.1% topical application of tacrolimus ointment was preferred and proved to be beneficial in relieving symptoms.…”
Section: Volume 6 Issue 4 -2017mentioning
confidence: 99%